The influence of workplace learning on employees' job satisfaction in Agrobank headquaters, Kuala Lumpur / Noraidza Arshad - Arshad, Noraidza (2014)
This research examines the influence of workplace learning on their job satisfaction among employees of Agrobank headquarters in Kuala Lumpur. In addition, the research aims to investigate the degree of workplace engagement that the employees are experiencing or satisfied in their work, to identify the workplace underlying factors and to gauge the differences in the degree of workplace learning engagement and job satisfaction for different demographic variables. The study was conducted using mixed-methods research where both questionnaire survey and structured interview were applied. Fifty (50) respondents took part in this survey and ten (10) employees were interviewed. The findings indicated that the degree of workplace learning engagement among the employees in general was at medium-high level with incidental learning as the most dominant factors in influencing employees’ workplace learning and there was no significant difference in the degree of workplace learning engagement for different demographic variables of gender, age group and position held. The overall level of job satisfaction was at medium level. Although female employees were reported to experience higher job satisfaction than the male employees however the mean difference between those two genders is very small. Thus it can be concluded that there was no significant difference in the level of job satisfaction for the three (3) demographic variables i.e. gender, age group and position held. The degree of workplace learning engagement experienced by the employees has a significantly positive relationship with their job satisfaction where an increase in employees’ workplace learning will result in an increase in job satisfaction (r = 0.80, p-value = 0.583) and employees agreed that workplace learning activities is an essential supportive factor for them to perform their job better. This findings are hoped will contribute to the general knowledge and understanding on employees’ workplace learning and how its influence their job satisfaction, and benefit the bank employees, management and training department in paying more attention of the dynamic nature of workplace learning in their organization.